Gênero artigo de opinião na perspectiva sócio-retórica - Silva, Antonio Ribeiro (2008)
The research made in this work have the general objective to analyse the genre opinion article under the social-rethorique perpective of text genre. Between the specific objectives, three of them to become detached. The first is to analysis the situation context of production and reception of opinion article. The second is to analysis the linguistic elements that implicate in the argumentative procedures of the text that performs the genre here in question. The third specific objective, associate with the second, is to analysis the argumentative pluralism present in the opinion articles that compose the seleccioned corpus. With this purpose, the analysis is divided in five stages, in which are distributed the social-discursive and the structure-linguistic elements that determine the argumentation. In this manner, twenty articles published by Folha de S. Paulo and Diário do Grande ABC pass for the analysis process. Writer and reader involved with in the interation process of opinion article were interviwed; in order to obtained informations about the interation situation of the article. The main justification of this work is offer subsidies to a complete undertanding of this genre, concerning the linguistic, discursive, social and argumentative aspects. As results of this analysis, to become destached the elucidations obtained about the production and reception context here in question, the interaction betweem the productor of the genre and the reader, farther determined historic aspects in the discursive comunity where circulate the opinioon article. About the linguistc-stuctural elements boarded for the argumentatios study present in this genres. to become destached the degree of argumentative pluralism that were possible detect in the two genre collection of the corpus